Gestor documental en la unidad de documentación y archivo de la Espam MFL - Cedeño Mendoza, Tito Argenis (2016)
The objective of this project was to design a prototype of document manager for the archive area in the Escuela Superior Politécnica Agropecuaria de Manabí Manuel Félix López. The DIRKS (Designing and Implementation Recordkeeping Systems) methodology was used. Its structure has eight stages from which seven were used. The stage A is the Preliminary Investigation, a checklist for the department requirements. Stage B called Organization Analysis Activities, the archive department process was studied. A comparative analysis for the document manager was implemented with Alfresco, Quipux and Nuxeo, among them Alfresco was chosen, for the database MYSQL manager was used. Stage C named Identification of Requirements were analyzed within its department activities. Stage E designed Identification of Strategies to get requirements, some strategies were defined for this activities. Stage F called Design of a Documents Management Systems had some adaptations on the system according to the requirements for the area. Stage G, implementation of a manager document system, installation and running software, also the workers were trained. Stage H, post implementation review to check system running. As a result, the documentation area had a system with optimum storage and an easy searching of files.